Pengaruh Likuiditas, Profitabilitas Dan Ukuran Perusahaan Terhadap Struktur Modal Pada Perusahaan Sub Sektor Batu Bara Yang Terdaftar Dibursa Efek Indonesia Tahun 2016-2021 - Siti Nur Maulani; Diah Yudhawati; Titing Suharti (Jurnal Ekonomika Dan Bisnis (JEBS), 2023)
This study aims to determine the effect of liquidity, profitability and company size on the capital structure of coal subsector companies on the Indonesia Stock Exchange. The research method used is a quantitative method using secondary data. The population in this study are coal mining companies listed on the Indonesia Stock Exchange in 2016-2021. The samples used were 8 companies using purposive sampling method. The objects in this study are companies in the coal sector (PT. Adaro Energy Tbk, PT. Bayana Resources Tbk, PT. Delta Dunia Makmur Tbk, PT. Golden Energy Mines Tbk, PT. Baramulti Suksessana Tbk, PT. Dian Swastika Sentosa Tbk. , PT Harum Energy Tbk, and PT Petrosea Tbk) which are listed on the IDX. In this study several variables were used including the dependent variable and the independent variable, which included the independent variables namely liquidity, profitability and firm size while the dependent variable included capital structure. Data analysis used panel data linear regression analysis, analysis of the coefficient of determination and the t test (partial) and the f test (simultaneous). The results of the partial test or t test each of the variables of liquidity and profitability have a significant effect on capital structure, and company size has no significant effect on capital structure. While the f (simultaneous) test shows that liquidity, profitability and firm size have a significant effect on capital structure.